Sulla simbiosi spazio-corporea all’esempio di „Treno di panna” e „Tecniche” - Kornacka, Barbara (My University, 2012)
The article About the Symbiosis of the Space and the body on the example of „Treno di panna” and „Tecniche di seduzione” by Andrea De Carlo is the analysis of space related to physicality in two novels by a contemporary Italian writer. An animate body expressing emotions and succumbing to the influences of the milieu’s moods becomes engaged in bilateral relations with space; the body integrates with it as well as interferes in it, exceeding its own spatial constraints. The article is also a suggestion to read contemporary Italian prose through the prism of the theory of a German neophenomenologist Hermann Schmitz. The most important issues of Schmitz’s theory are presented and illustrated from the literary perspective: the notion of the Lieb i.e. the body which is alive, dynamic and perceives; the notion of feelings seen as atmospheres which are spatial feelings; and the concept of the living space. The analyzed examples illustrate the compatibility of the Italian writer’s literary intuition with the newest philosophical theories.
Keywords: Hermann Schmitz; Andrea De Carlo; body; space